2015
DOI: 10.1080/0163853x.2015.1025665
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comprehension of Text Information: Two Sides of the Same Coin

Abstract: In psychological research, the comprehension of linguistic information and the knowledge-based assessment of its validity are often regarded as two separate stages of information processing. Recent findings in psycholinguistics and text comprehension research call this two-stage model into question. In particular, validation can affect comprehension outcomes, and the comprehension process involves a routine and early validation of the communicated information. These findings suggest that the comprehension and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 63 publications
(69 reference statements)
7
59
1
8
Order By: Relevance
“…These processes are assumed to operate in a parallel but asynchronous manner; validation starts only after the process of integration has begun (see also O'Brien & Cook, 2016). Based on a range of empirical findings, Richter (2015) argues that validation is perhaps even more closely interwoven with integration, 3 These surprisal values are calculated for the depicted word-by-word transitions, and they may differ slightly from the averaged surprisal values shown in Figure 10.…”
Section: Comprehension As Situation-state Space Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes are assumed to operate in a parallel but asynchronous manner; validation starts only after the process of integration has begun (see also O'Brien & Cook, 2016). Based on a range of empirical findings, Richter (2015) argues that validation is perhaps even more closely interwoven with integration, 3 These surprisal values are calculated for the depicted word-by-word transitions, and they may differ slightly from the averaged surprisal values shown in Figure 10.…”
Section: Comprehension As Situation-state Space Navigationmentioning
confidence: 99%
“…On the empirical front, a wide range of findings has shown that the processing difficulty of individual words is affected by the larger discourse context and general knowledge about the world, above and beyond linguistic experience alone (see, e.g., Albrecht & O'Brien, 1993;Altmann & Kamide, 1999;Camblin, Gordon, & Swaab, 2007;Cook & Myers, 2004;Garrod & Terras, 2000;Hess, Foss, & Carroll, 1995;Knoeferle, Crocker, Scheepers, & Pickering, 2005;Knoeferle, Habets, Crocker, & Münte, 2008;Kuperberg, Paczynski, & Ditman, 2011;Morris, 1994;Myers & O'Brien, 1998;O'Brien & Albrecht, 1992;Otten & van Berkum, 2008;van Berkum, Brown, Zwitserlood, Kooijman, & Hagoort, 2005; van Berkum, Hagoort, & Brown, 1999;van Berkum, Zwitserlood, Hagoort, & Brown, 2003). As such, recent theories of text comprehension have emphasized the importance of world knowledge on incremental comprehension by arguing that the validation of message consistency is a central part of the comprehension process (Cook & O'Brien, 2014;Isberner & Richter, 2014;O'Brien & Cook, 2016;Richter, 2015;Singer, 2006Singer, , 2013Singer & Doering, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Readers use their knowledge and beliefs not only for interpreting and encoding text information but also for monitoring its validity. This process, which has been called epistemic monitoring (Isberner & Richter, 2014a) or validation (Richter, 2015;Singer, 2013), seems to be a routine part of comprehension activities. The modifier "epistemic" in epistemic monitoring clarifies that this kind of monitoring refers to the epistemic status of information (in contrast to the kind of comprehension monitoring that has been the focus of metacomprehension research; Baker, 1979).…”
Section: Validation In Text Comprehensionmentioning
confidence: 99%
“…In this article, we suggest that readers' prior beliefs affect multiple documents processing (partly) as a consequence of routine cognitive processes that continuously monitor incoming information for its consistency with currently active knowledge and beliefs, as well as currently active information from previously read text(s). In the text comprehension literature, these processes have been termed validation (Richter, 2015;Singer, 2013) or epistemic monitoring (Isberner & Richter, 2014a). The basic idea, which is elaborated in the next section, is that such validation processes are a regular component of comprehending texts.…”
Section: Comprehension Of Multiple Documents With Conflicting Informamentioning
confidence: 99%
See 1 more Smart Citation